Improving Health Administration Capacity and Community Nutrition Education to Mitigate the Risk of Environmentally-Based Diseases - Utami; Antik Pujihastuti (Sustainable Applied Modification Evidence Community (SAMEC), 2024)
A World Health Organization (WHO) report highlights that non-communicable diseases (NCDs), such as diabetes, hypertension, and cardiovascular diseases, accounted for approximately 71% of all deaths globally by 2020. This research focuses on enhancing the capacity of health administration in managing community nutrition education programs to mitigate disease risk in vulnerable populations. Utilizing quantitative methods, the study employs t-tests to evaluate the effectiveness of nutrition education counseling before and after implementation.The sample comprised 27 individuals selected through purposive sampling. Data analysis revealed a notable increase in students' understanding of environmental sanitation, rising from 79.3% in the pretest to 85.93% in the posttest. Additionally, health workers exhibited a 20% improvement in knowledge regarding environmental diseases following program implementation. Compliance with sanitation and hygiene policies increased by 22%, indicating successful enforcement of stricter sanitation measures aimed at reducing environmental disease risks.Moreover, significant improvements were observed in water quality monitoring (25%) and routine training (28%), demonstrating the program's effectiveness in strengthening administrative systems to minimize disease risks. This study underscores that enhancing health administration capacity and community nutrition education through counseling and regular training effectively reduces environment-based disease risks. Ongoing education and consistent monitoring of the program’s long-term impact are essential for sustainability. Ultimately, this program serves as a promising model for future environmental health prevention efforts, emphasizing the importance of community engagement and education in combating NCDs.